Bio-funcional components in mushrooms, a health opportunity: Ergothionine and huitlacohe as recent trends. (February 2021) - Martinez-Medina, Gloria A.; Chávez-González, Mónica L.; Verma, Deepak Kumar; Prado-Barragán, L. Arely; Martínez-Hernández, Jose L.; Flores-Gallegos, Adriana C.; Thakur, Mamta; Srivastav, Prem Prakash; Aguilar, Cristóbal N.
Graphical abstract: Highlights: Mushrooms are a source of functional molecules for diverse system-levels. Huitlacoche is a low explored Mexican edible mushroom with potential health benefits. Ergothionine shows meaningful attributes, relevant in health and food fields. Huitlacoche could propel economic, health, pharmaceutical and agricultural growth. Abstract: Macrofungi, mushrooms or higher fungi have been employed for medicinal and food purposes for decades, nevertheless, also represent, a novel and fruitful source of biologically relevant compounds, that could serve as health enhancers in diverse human illness conditions; specially, mushrooms, are considered a relevant source of the distictive molecule – ergothioneine, an excellent supply of important antioxidant, which boosts human health and shows potential as a preservative in food, promoting their utilization as functional foods, in this context, the present review overviews and complies current knowledge and trends of nutrients as well as bioactive mushroom components including the potential of Huitlacoche and ergothioneine, and the possible health benefits of these biological products and their activities have been explored which enhances the utilization of mushrooms.